Discharge Coefficient for Trapezoidal Labyrinth Side Weir in Subcritical Flow - Emiroglu, Muhammet Emin; Kaya, Nihat (Springer, 2011)
The discharge coefficient of a trapezoidal labyrinth side weir is a function of the Froude number F (1), the dimensionless effective crest length L/a, the dimensionless weir length L/B, the dimensionless weir height p/h (1), and the sidewall angle alpha. A labyrinth weir is an overflow weir, folded in plan view to provide a longer total effective length for a given overall weir width. These weirs have advantages compared to the straight overflow weir and the standard ogee crest. Previous studies on the subject have generally focused on rectangular side weirs located on a straight channel. The present study investigates the hydraulic behavior of a trapezoidal labyrinth side weir. The results show that the discharge coefficient of labyrinth side weirs gives a significantly higher coefficient value compare to that of conventional straight side weirs. Discharge coefficient of the trapezoidal labyrinth side weir is 1.5 to 5.0 times higher than the conventional straight side weir. Consequently, an equation for the coefficient of discharge is introduced. The results predicted by the equation were shown to be very satisfactory using root mean square error (RMSE), mean absolute error (MAE) and correlation coefficient (R) statistics.
Keywords: Side weir; Water discharge; Discharge coefficient; Intake; Labyrinth weir; Channel flow